2021
DOI: 10.1111/mec.15877
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting levels of genetic predictability in the evolution of resistance to major classes of fungicides

Abstract: The extent to which evolution is predictable, both phenotypically and at a genetic level (Stern & Orgogozo, 2009), has wide-ranging implications in evolutionary biology, especially in systems such as pathogens and cancers, where predicting future evolution would enable the design of more durable treatments (Lässig et al., 2017). The emergence of resistance to drugs and pesticides is an example of rapid, contemporary evolution. It has important practical implications for human health and wellbeing, both directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…Parallel evolution is frequent in fungicide resistance (Hawkins et al ., 2019). A review of literature suggests that lab mutations associated with high RFs, and those found in multiple species, are more likely to be reported in the field (Hawkins and Fraaije, 2016, 2021). Altogether, our findings make the selection of G37V a realistic and most probable evolutionary scenario for Z. tritici populations exposed to fenpicoxamid selection pressure in the field, and suggest this could occur in both QoI-sensitive and resistant populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel evolution is frequent in fungicide resistance (Hawkins et al ., 2019). A review of literature suggests that lab mutations associated with high RFs, and those found in multiple species, are more likely to be reported in the field (Hawkins and Fraaije, 2016, 2021). Altogether, our findings make the selection of G37V a realistic and most probable evolutionary scenario for Z. tritici populations exposed to fenpicoxamid selection pressure in the field, and suggest this could occur in both QoI-sensitive and resistant populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of QoIs, their repeated and unrestricted use in the field (Bartlett et al ., 2002) quickly triggered the emergence of target site resistance in many fungal pathogens. This rapid emergence and spread occurred in multiple species (Hawkins and Fraaije, 2021), and had not been predicted. The most common resistance mutation leads to the G143A change, and has been selected in Z. tritici (Fraaije et al ., 2005) and repeatedly in many other pathogens (Hawkins and Fraaije, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Predictability (in the sense of repeatability) is also studied in the context of parallel or convergent evolution in natural systems. Examples of this approach include the emergence of drug-resistant pathogens in different patients (Lieberman et al 2011, Feder et al 2021, and herbicide resistance in different species or geographic areas (Kreiner et al 2019, Hawkins & Fraaije 2021.…”
Section: Predictabilitymentioning
confidence: 99%
“…This rapid emergence and spread occurred in multiple species (Hawkins and Fraaije, 2021), and had not been predicted. The most common resistance mutation leads to the G143A change, and has been selected in Z. tritici (Fraaije et al, 2005) and repeatedly in many other pathogens (Hawkins and Fraaije, 2021). In Z. tritici, resistance is now generalized in populations from Western Europe (Garnault et al, 2019;Kildea et al, 2019).…”
Section: Introductionmentioning
confidence: 97%